Desain Sistem Pengelolaan Sampah Organik pada PT. XYZ Menggunakan Metode Supply Chain Management - Saputra, Muhammad Fasha Rizky; Arsiwi, Pramudi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The accumulation of waste in Indonesia continues to increase over time, especially organic waste such as food waste. With the environmental problems being faced in Indonesia, PT. XYZ provides a solution so that this problem can be helped. PT. XYZ is a start-up that focuses on developing bioconversion technology using Black Soldier Fly (BSF) or maggot flies to process organic waste into high-value products. Supply chain flow is very important in the production process so that the flow from supplier to consumer is structured. Based on observations that have been made, several problems were found at PT. XYZ, namely that there are problems when collecting waste from partners A, B, C, D, and E because these partners are located far from each other so that the arrival of organic waste at PT. XYZ there was a delay. So that these problems can be overcome, it is necessary to approach the problem using the Supply Chain Management method so that the flow of the supply chain can be mapped so that the problem can be resolved. The results of this research obtained a cost reduction of 41.9% after implementing this solution.